Nilai Kesesuaian Produk Non-Makanan dan Produk Makanan Berstandar Nasional Indonesia (SNI) di Malang, Gresik, Blitar, Tulungagung, dan Pasuruan - Ismail, H. M. (Jurnal Aplikasi Manajemen, 2011)
This study aims to: (1) Identify the products that have been standard SNI, (2) Conducting an analysis of the suitability of the product is whether it is feasible to get ISO standards, (3) Provide recommendations which products really fit with the standard status SNI and products which are still less worthy of the status of ISO standard. This research approach is quantitative with survey method. Instruments used in the implementation of a questionnaire survey. The results of this study are as follows: (1) There are clear criteria in determining the SNI products, and information obtained by the parties concerned can be accessed easily, (2) In the two components of the survey, namely non-food products and food products, all respondents said that stakeholders can participate in the development of SNI, (3) There is transparency in the development of SNI ranging from programming and formulation stage to the stage of establishment, (4) On average, respondents said that the stakeholders can give their interests and treated fair; (5) Trading facility provided by the national government in order to standardize considered effective and relevant, (6) There is a connectedness in the development of national standardization. In the two components of the survey contained figure of 2.83 in non-food products and 2,76 on the food products, (7) National standardization program that also consider the public interest and also national interest was also considered by respondents to have dimensions of development, (8) An increasing Index Standard Suitability Test Items from the year 2008-2010, although the range in 2007-2008 has decreased, (9) Index Standard Product Suitability Test in Malang, Gresik, Blitar, Tulungagung, dan Pasuruan viewed from statistical data presented in general belong to the category of "good", (10) For products already in the survey, referring to the results of statistical data, it deserves to get the label of SNI from stakeholders.